Educação em direitos humanos: um desafio global em uma perspectiva local - Costa, Laisa Quadros da (2016)
Educating for Human Rights, besides being one of the principles and goals of education in Brazil, has its obligation fixed in law and should be inserted in the projects, plans and teaching materials at all levels and modalities and addressed in a transversal perspective, disciplinary and/or interdisciplinary. Given this premise and the need to spread a culture of respect for the dignity of the human person and the promotion of values such as freedom, justice, equality, solidarity, cooperation, peace, sustainability and social rights, economic, political and cultural, this research objective reflection on the laws, public policy and teaching practices in this subject. The study with qualitative and quantitative approach, supported by bibliographic sources, documentary and auto (biographical), transits questions on Education and Human Rights, the role of the State and Society, points out the relevant legislation to the point of meeting the teachers and students of the Teacher’s Training Graduate Special Program for Vocational Education of the Federal University of Santa Maria which report how the rules are understood and incorporated into their everyday life and their teaching practices. Among other aspects, the research showed that most of the interviewees understand Human Rights Education as fundamental or important, students perceive the insertion of the themes in the disciplines and tell how it happens and the teachers confirm the students' responses and tell their experiences and perceptions. Some shortcomings were found such as: difficulties in understanding some concepts in the area, some important issues to Human Rights were little discussed and the need for improvement in existing communication on the dissemination of new legislation. The experiences are used to create study units, which highlight the opportunities and challenges faced in order to contribute to the reflection and improvements in public policy, educational process and conditions of collective life that requires new perspectives in promoting peace and preservation of the man and the environment, where relationships are more human.